An Erupted Dilated Odontoma: A Rare Presentation - Gaurav Sharma; Amritpreet Nagra; Gurkeerat Singh; Archna Nagpal; Atul Soin; Vishal Bhardwaj (Case Reports in Dentistry)
A dilated odontoma is an extremely rare developmental anomaly represented as a dilatation of the crown and root as a consequence of a deep, enamel-lined invagination and is considered a severe variant of dens invaginatus. An oval shape of the tooth lacking morphological characteristics of a crown or root implies that the invagination happened in the initial stages of morphodifferentiation. Spontaneous eruption of an odontoma is a rare occurrence and the occurrence of a dilated odontoma in a supernumerary tooth is even rarer with only a few case reports documented in the English literature. We present an extremely rare case of erupted dilated odontoma occurring in the supernumerary tooth in anterior maxillary region in an 18-year-old male, which, to the best of our knowledge, is the first ever case reported in English literature.